Intercritical circulating levels of neo-epitopes reflecting matrixmetalloprotease-driven degradation as markers of gout and frequent gout attacks. (2nd June 2016) - Valdes, Ana M.; Manon-Jensen, Tina; Abhishek, Abhishek; Jenkins, Wendy; Siebuhr, Anne Sofie; Karsdal, Morten A.; Doherty, Sally; Zhang, Weiya; Richardson, Helen; Doherty, Michael; Bay-Jensen, Anne-Christine
Abstract: Objective. Recurrent flares constitute the main clinical burden of gout. Our aim was to assess whether biomarkers measuring MMP tissue degradation could be used as markers of frequent gout flares. Methods. Fasting plasma samples from 112 men with gout and 170 controls, along with serum samples from 447 men with gout collected at baseline from an ongoing clinical trial, were analysed by ELISA for neo-epitopes from MMP degradation of collagens type I (C1M) and type III (C3M). The log 10 levels of both markers were compared between cases and controls and between gout patients with three or more gout attacks in the past year and those with two or less attacks. Results. The circulating levels of C1M and C3M correlated with gout status in the case–control study. Levels of both markers were associated with frequent gout flares (⩾3 attacks in the past year) in both cohorts (odds ratio, OR = 3.1; 95% CI: 1.4, 6.8; P = 0.0056 for log 10 C1M, and OR = 6.7; 95% CI: 2.3, 19.3; P = 0.0005 for log 10 C3M). The area under the curve in a receiver operating characteristic analysis of frequent flares increased from 0.68 to 0.74 in one cohort and from 0.60 to 0.66 in the other when log 10 C1M and log 10 C3M were added to clinical variables of the model. Conclusion. C1M and C3M, reflective of interstitial matrix destruction, are associated with gout status and with frequent gout flares in men, suggesting that increased MMP activity may contribute to gout flares. Further research is needed to find out whether this is independent of dietary and lifestyle risk factors for acute gout.